2001
DOI: 10.1046/j.1365-201x.2001.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite‐derived nitric oxide: a possible mediator of ‘acidic–metabolic’ vasodilation

Abstract: The fundamental, yet poorly understood, physiological mechanism known as 'acidic-metabolic' vasodilation, contributes to local blood flow regulation during hypoxia/ischaemia and increased metabolic activity. The vasodilator nitric oxide (NO) has been suggested to be involved in this event. Besides enzymatic production by NO synthases, a novel mechanism for generation of this gas in vivo was recently described. This involves non-enzymatic reduction of inorganic nitrite to NO, a reaction that takes place predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(127 citation statements)
references
References 34 publications
3
123
0
1
Order By: Relevance
“…But could nitrite be bioactive also at much lower physiological levels? In 2001 Modin et al first reported on vasoactivity from physiological amounts of nitrite (Modin et al, 2001). Rat aortic strips dilated when exposed to low micromolar levels of nitrite, if the medium had been made slightly acidic (pH ~7).…”
Section: Systemic Generation Of No From Nitritementioning
confidence: 98%
“…But could nitrite be bioactive also at much lower physiological levels? In 2001 Modin et al first reported on vasoactivity from physiological amounts of nitrite (Modin et al, 2001). Rat aortic strips dilated when exposed to low micromolar levels of nitrite, if the medium had been made slightly acidic (pH ~7).…”
Section: Systemic Generation Of No From Nitritementioning
confidence: 98%
“…In contrast, Wilkerson et al (2012) observed no difference in power output during the earlier stages of a 50 mile (total exercise duration: >2 h) cycle ergometry TT, yet the final 10 miles was faster with NO 3 − supplementation. Together, these findings might suggest a potential application of BRJ during higher work rate periods within a longer duration event, perhaps specifically those which require greater type II muscle recruitment or markedly decrease the muscle pH and PO 2 and hence, augment NO 2 − reduction into NO (Modin et al 2001;Cosby et al 2003;Castello et al 2006). This might include facilitating a fast start or finish during competition, or responding to a surge by another competitor.…”
Section: Effects Of Brj On 10000 M Tt Performancementioning
confidence: 99%
“…This suggests that it is differences in the 'use' rather than the availability of NO 2 − that is important. This might be related to greater acidosis and hypoxia, and thus NO 2 − reduction (Modin et al 2001;Cosby et al 2003;Castello et al 2006), in the 1500 vs. 10,000 m conditions, as a consequence of the relatively greater work rate adopted (~86 vs. 78% V O 2max ; ~6.5 vs. 4.5 mM blood [Lactate]). …”
Section: Effects Of Brj On Plasma [No 2 − ] and Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…A handful of enzymatic and nonenzymatic pathways have been demonstrated to catalyze nitrite reduction to NO in blood and tissues, including deoxyhemoglobin and deoxymyoglobin [6,7], aldehyde oxidase (AO) [8], aldehyde dehydrogenase (ALDH) [9][10][11], xanthine oxidoreductase (XOR) [12,13], and endothelial NO synthase (NOS) [14]. Nitrite has enhanced bioactivity at low oxygen tensions and under acidic conditions [6,15,16], and studies have demonstrated a protective effect of this anion in ischemia-reperfusion injury [17,18].…”
Section: Introductionmentioning
confidence: 99%